Perancangan Sistem Informasi Konsultasi Akademik Berbasis Website - Manuhutu, Melda; Wattimena, Juneth (Universitas Diponegoro, 2019)
In this era of modernization, a successful consultation process can increase its efficiency and effectiveness by utilizing information technology that has been successfully developed by the internet. The development of computer technology, encouraged communities and groups to compete to improve the quality of their services in various fields. Awareness of this must also be used by the Higher Education Institution as a student provider. The computerized Academic Consultation System that is used through the internet network is needed to facilitate students to carry out the coaching process together with academic advisors. This system is very easy to control and evaluate as a whole based on the College Leaders or other implementers at the Faculty level. The system development model used in this study is model prototypes and data collected through observation, interviews and literature. The programming language used is PHP and the software interface for designing using Adobe Dreamweaver CS. Making a database using MySQL with the XAMMP application. The system testing was using black box testing and the results found that the system can run well and in accordance with their respective functions.